(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Speech etiquette represents an important component of communicative culture and reflects social norms, traditions, and cultural values of a particular linguistic community. The present study focuses on a comparative analysis of speech etiquette in English and Uzbek languages. The research examines typical forms of greetings, farewells, requests, apologies, and expressions of gratitude used in everyday communication. The analysis reveals both similarities and differences between the two languages, which are conditioned by cultural, social, and historical factors. The findings demonstrate that speech etiquette serves not only as a linguistic phenomenon but also as a reflection of national mentality and communicative behavior.